Review of rhythm disturbances in patient after fontan completion: epidemiology, management, and surveillance - Wall, Kevin; Hebson, Camden; D’Souza, Roshan; Balaji, Seshadri (Frontiers in Pediatrics, 2025)
PurposeThe Fontan operation is commonly associated with alterations in heart rhythms, both tachycardic and bradycardic. Despite modifications to attempt to mitigate these complications, arrythmias still frequently occur. The purpose of this review is to examine the literature regarding the scope of the problem, therapeutic options, and current recommendations regarding screening and surveillance.Recent findingsModifications to the original Fontan procedure, antiarrhythmic medications, and improvements in catheter ablation procedures have improved the management of patients with arrhythmias following Fontan palliation. There is growing interest in the role of junctional rhythm in the role of Fontan dysfunction. While chronotropic incompetence has often been blamed for poor exercise testing, there is evidence that decreased performance may be related to ventricular filling and Fontan hemodynamics.SummaryTachyarrhythmias are an important cause of mortality and morbidity after the Fontan operation. Prompt and aggressive management of arrhythmias with the goal of maintaining sinus rhythm is vital. Management strategies such as anti-arrhythmic medications, ablation, anti-tachycardia pacing and Fontan conversion should be seen as complementary and used early to prevent hemodynamic deterioration. Bradyarrythmias likely also contribute to Fontan failure. Pacing is the primary management strategy with evidence supporting use of atrial pacing. However, ventricular pacing seems to often lead to deleterious effects. Current guidelines recommend surveillance with Holter monitor every 2–3 years in adolescents and every 1–2 years in adults. Future directions for research include further assessment of junctional rhythm and its management as well as further identifying patients in which pacing would be beneficial.